Contemporary States and the Pandemic - Itrich-Drabarek, Jolanta (Taylor & Francis, 2023)
This volume elaborately studies the challenges posed and impact made by the Covid 19 pandemic. Through detailed case studies, it presents ethical, political, economic, medical, logistical and social impediments faced by contemporary states in the EU. The book focuses on the short and long-term consequences of the economic shock caused by the COVID-19 pandemic and covers issues concerning the world economy, the EU economy, as well as the Visegrad economies. The essays in this volume: Probes into the response of states to the economic phenomena resulting from the pandemic and analyses the institutional framework of the resulting crisis, lapses in social communication, social protests and the decline in democratic standards in countries such as the Czech Republic, Poland, Slovakia, and Hungary; Discusses issues related to state security under conditions of the pandemic, the effectiveness of state and self-government administration, the transition of states from an external controllability to an internal controllability model of power, as well as challenges related to security in the digital space; Presents policy actions at three basic levels, i.e. at the global, regional and sub-regional, and investigate strategies of the UN, WHO, the EU and the Visegrad Group as they play the most important role in the fight against COVID-19; This insightful and timely volume will be of great interest to scholars, researchers and anyone inquisitive about political theory, public policy, public health and social care, international relations, governance, security studies, and public administration.